Assessing the Impact of Community-Based Oral Health Education Programs on Dental Hygiene Practices and Oral Health Outcomes in Rural Populations - Swapnil S. Bumb; Pushparaj Singh; Sahana Maben; Prasannasrinivas Deshpande; Mrinal V. Limaye; Hanadi A. Alwafi (Journal of Pharmacy and Bioallied Sciences)
Background: Community-based oral health education programs are essential in improving dental hygiene practices and oral health outcomes, particularly in rural populations where access to dental care is limited. This study assesses the impact of such programs on dental hygiene practices and oral health outcomes in rural communities. Materials and Methods: A quasi-experimental design was employed to evaluate the effectiveness of a 6-month oral health education program conducted in five rural villages. A total of 300 participants, aged 18-60 years, were selected through stratified random sampling. The intervention included bi-weekly educational sessions on oral hygiene practices, proper brushing techniques, and the importance of regular dental check-ups. Data on dental hygiene practices were collected through structured questionnaires at baseline and post-intervention. Oral health outcomes were assessed using the Decayed, Missing, and Filled Teeth (DMFT) index and gingival health was evaluated through gingival index scores. Results: Post-intervention analysis showed a significant improvement in dental hygiene practices among participants, with 75% reporting regular brushing compared to 45% at baseline. The mean DMFT score decreased from 5.2 to 3.8 (P < 0.05), and the average gingival index score improved from 2.1 to 1.4 (P < 0.05). Additionally, the frequency of dental check-ups increased by 40%, indicating a positive behavioral shift in the community. Conclusion: Community-based oral health education programs significantly improve dental hygiene practices and oral health outcomes in rural populations.